‘Scientists Like Me’: Using Culturally Relevant Information Literacy Instruction to Foster Student STEM Identity - Sheena Campbell; Nancy Wallace (Issues in Science and Technology Librarianship, 2024)
In this case study, two librarians reflect upon our efforts to design STEM-focused information literacy instruction for undergraduate students at an R1, land grant university. Designed around the principles of culturally relevant pedagogy, our curriculum integrates community-focused and regionally specific topics reflecting our students' lived experience, features the work of scientists from diverse backgrounds, and fosters discussions about equity in the library classroom. Our experience shows that this approach can help foster STEM identity development in students while strengthening inquiry-based learning through information research.